CONTAGION DYNAMICS IN THE IRANIAN STOCK MARKET - Samad Sedaghati, Ruhollah Farhadi, Mir Feyz Fallashamss (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Contagion in financial markets takes place both because of fundamental or non-fundamental reasons like herd behaviors that can increase market risk levels and even end in inefficient allocation of financial resources. Thus, understanding the contagion and its dynamics will be critical for the participants of financial market. Hence, using network-based epidemic modeling, the study examined the dynamics of contagion in the Iranian stock market from 2011 to 2019 and short-term and long-term scales. To this end, first the correlation network of 46 Iranian stock market groups was developed and then analyzed using short-term and long-term contagion dynamics simulations. The results showed that the extent and speed of contagion is much higher in the short-term than in long-term and in long-term a significant number of groups can be immune to the contagion. However, in long-term the rate of return to pre-contagion status is shorter than in short-term.